Evaluasi Indeks Ketahanan Sosial Sebagai Bagian Dari Penerapan Program Indeks Desa Membangun di Kabupaten Ogan Ilir - Faisal Nomaini (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2019)
Building Villages Index (IDM) has become a relatively new form of the program implemented by the government to find out the extent of village capacity development. One of the variables measured in IDM is Social Resilience Index (IKS) which is the main topic in this paper. The theoretical assumption applied is the measurement of social security in villages through IKS which is commonly carried out only on a nominal measurement scale, while IKS in this study was measured on an interval measurement scale to produce a gradual outcome of village social resilience. This study was conducted using a quantitative design by measuring the four dimensions of IKS in Lorok Village, Ogan Ilir Regency. Descriptive analysis and univariate analysis are part of the statistical calculations performed. The results again that only one out of 4 dimensions of IKS obtained the high-level category, namely the educational dimension. While the dimensions of social capital, health, and settlements only reached into the medium category. The following result shows that the level of achievement for the overall Social Resilience Index Variable is moderate, with a percentage of achievement of 57.79%